Electrophysiological and Pharmacological Analyses of Nav1.9 Voltage-Gated Sodium Channel by Establishing a Heterologous Expression System - Zhou, Xi; Xiao, Zhen; Xu, Yan; Zhang, Yunxiao; Tang, Dongfang; Wu, Xinzhou; Tang, Cheng; Chen, Minzhi; Shi, Xiaoliu; Chen, Ping; Liang, Songping; Liu, Zhonghua (Frontiers in Pharmacology, 2017)
Nav1.9 voltage-gated sodium channel is preferentially expressed in peripheral nociceptive neurons. Recent progresses have proved its role in pain sensation, but our understanding of Nav1.9, in general, has lagged behind because of limitations in heterologous expression in mammal cells. In this work, functional expression of human Nav1.9 (hNav1.9) was achieved by fusing GFP to the C-terminal of hNav1.9 in ND7/23 cells, which has been proved to be a reliable method to the electrophysiological and pharmacological studies of hNav1.9. By using the hNav1.9 expression system, we investigated the electrophysiological properties of four mutations of hNav1.9 (K419N, A582T, A842P and F1689L), whose electrophysiological functions have not been determined yet. The four mutations significantly caused positive shift of the steady-state fast inactivation and therefore increased hNav1.9 activity, consistent with the phenotype of painful peripheral neuropathy. Meanwhile, the effects of inflammatory mediators on hNav1.9 were also investigated. Impressively, histamine was found for the first time to enhance hNav1.9 activity, indicating its vital role in hNav1.9 modulating inflammatory pain. Taken together, our research provided a useful platform for hNav1.9 studies and new insight into mechanism of hNav1.9 linking to pain.